Faktor-Faktor yang Mempengaruhi Preferensi Anak Pekerja Migran Indonesia untuk Bekerja ke Luar Negeri di Kabupaten Cilacap - Merlin Cindiana; Dedi Supriadi; Herman Sambodo (Ekonomis: Journal of Economics and Business, 2022)
This study aims to analyzing the preferences of Indonesian migrant workers children to work abroad in Cilacap Regency, analyzing the factors affecting the preference of Indonesian migrant workers children to work abroad in Cilacap Regency, and analyzing differences in preferences of Indonesian migrant workers children to work abroad in Cilacap Regency based on demographic characteristics. Preferences of Indonesian migrant workers children to work abroad became dependent variable, meanwhile income, education, age, gender, and marital status as independent variable. The data collection method used purposive sampling with 100 samples and use multiple linear regression analysis model. The results obtained are: the indicators of preference for opening a new business, land and house ownership are more dominant than other indicators preference to work abroad. Income, education, age, gender, and marital status have an effect toward preferences of Indonesian migrant workers children to work abroad. There is difference in preferences of Indonesian migrant workers children to work abroad based on demographic characteristics.